1971
DOI: 10.1021/i160039a007
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Benzene in Carbon Slurries

Abstract: Experimental rates have been measured at 24°C for the solution of benzene from gas bubbles into water and aqueous slurries of activated carbon particles. Batch-type experiments were carried out so that the data at low time values gave from a single-resistance equation the mass transfer coefficient ki from gasbubble interface to bulk liquid. For bubbles whose diameter was 1.8 mm kt was about 4 X 10-2 cm/sec.The same value was obtained for the solution of benzene in water alone or in aqueous slurries of carbon p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…The requirement for this linearity is that the bubble size does not change with gas flow rate. The bubble diameter as measured by Misic and Smith (1971), over a range of Q values similar to those used in our experiment with a similar dispersion tube, did not change significantly.…”
Section: Methods Of Analysissupporting
confidence: 57%
“…The requirement for this linearity is that the bubble size does not change with gas flow rate. The bubble diameter as measured by Misic and Smith (1971), over a range of Q values similar to those used in our experiment with a similar dispersion tube, did not change significantly.…”
Section: Methods Of Analysissupporting
confidence: 57%
“…Hence, complete mixing was assumed for this phase. Even for an agitated slurry the bubble stream is not well mixed (Juvekar and Shanna, 1973;Misic and Smith, 1971). The latter authors showed that plug flow of gas well represented their data for benzene adsorption in an agitated, aqueous slurry of activated carbon.…”
Section: Adsorption Of Sulfur Dioxidementioning
confidence: 93%
“…Then, the liquid phase concentration at the gasliquid interface is that in equilibrium with the bulk gas value. Since Henry's law is valid for benzene in water at low concentrations and 298"K, the interface Concentration is C = CJH, where H = 0.20 (Misic and Smith, 1971). Also, the physical adsorption of benzene on activated carbon is intrinsically rapid.…”
Section: Theorymentioning
confidence: 99%
“…In using the zero moment data, a is first calculated from Equation (12), after /3 is evaluated from the liquid and gas flow rates and the Henry law constant. As mentioned, H was taken as 0.20 at 25°C (Misic and Smith, 1971). However, the value of a is not very sensitive to H ; a 60% change in the Henry law constant causes an 8% change in (ka),.…”
Section: Gas-to-liquid Mass Transfer Coefficient (Trickle Bed Data)mentioning
confidence: 99%